Exploration of Zakat Management Practices : A Qualitative study in Aceh's Mosques - Eka Octavian Pranata; Hafiizh Maulana (Jurnal I-Philanthropy, 2024)
Abstract Zakat, one of the five pillars of Islam, plays a pivotal role in alleviating pov-erty and promoting social justice within Muslim communities. In Aceh, where Islamic values are deeply rooted, mosques serve as key institutions for zakat collection and distribution. This qualitative study explores the zakat management practices in Aceh’s mosques, examining how mosque leaders and community members understand, im-plement, and evaluate zakat programs. Through in-depth interviews with mosque ad-ministrators, religious leaders, and zakat beneficiaries, this study sheds light on the challenges and opportunities in improving zakat management. The findings highlight the importance of transparency, community participation, and institutional support for effective zakat distribution.